Hydrothorax in fetal cases of Opitz G/BBB diagnosis: Extending the phenotype?. Issue 6 (14th September 2020) - Tessier, Aude; Boutaud, Lucile; Bruel, Ange‐Line; Thauvin‐Robinet, Christel; Roth, Philippe; Malan, Valérie; Beaujard, Marie‐Paule; Achaiaa, Amale; de Oliveira, Judite; Steffann, Julie; Encha‐Razavi, Ferechte; Faivre, Laurence; et al.
Abstract : We report two fetal cases carrying a de novo MID1 mutation and presenting with severe hydrothorax, suggesting the expansion of the phenotype of Opitz GBBB syndrome